2015
DOI: 10.1186/s12933-015-0200-9
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional analysis of serum calcium levels for associations with left ventricular hypertrophy in normocalcemia individuals with type 2 diabetes

Abstract: BackgroundLeft ventricular hypertrophy (LVH) is prevalent in patients with type 2 diabetes mellitus (T2DM). Recent studies show that an increase in albumin-adjusted serum calcium level is associated with an elevated risk of T2DM. We speculate that increased serum calcium levels in T2DM patients are related to LVH prevalence.MethodsIn this echocardiographic study, 833 normocalcemia and normophosphatemia patients with T2DM were enrolled. The associations between serum calcium and metabolic parameters, left ventr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 66 publications
2
15
0
Order By: Relevance
“…As a key pathophysiological mechanism of T2DM, insulin resistance is not only accompanied with an increase in intracellular calcium [ 34 , 35 ], but also positively correlated with serum calcium level in ours and other studies [ 33 , 36 , 37 ]. Meanwhile, there is increasing awareness regarding the associations of insulin resistance with myocardial diastolic dysfunction, cardiomyopathy and heart failure [ 21 , 38 , 39 ].…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…As a key pathophysiological mechanism of T2DM, insulin resistance is not only accompanied with an increase in intracellular calcium [ 34 , 35 ], but also positively correlated with serum calcium level in ours and other studies [ 33 , 36 , 37 ]. Meanwhile, there is increasing awareness regarding the associations of insulin resistance with myocardial diastolic dysfunction, cardiomyopathy and heart failure [ 21 , 38 , 39 ].…”
Section: Discussionsupporting
confidence: 70%
“…Though eccentric hypertrophy can occur in HFpEF, ours and previous studies [ 3 , 32 ] demonstrate that concentric hypertrophy is the common form of left ventricular structural abnormality observed in these patients. Furthermore, in patients with T2DM, serum calcium is associated with an increased risk of LVH [ 33 ]. In accord with these, patients in our study with concentric hypertrophy had a higher but not significant level of serum calcium (9.13 ± 0.40 vs. 9.05 ± 0.42 mg/dL, p = 0.083) and a greater percentage of HFpEF (28.7 vs. 16.7 %, p = 0.014) than those with eccentric hypertrophy; however, after adjusted for LVMI (the index for LVH), serum calcium remained significantly associated with HFpEF (Table 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with the report from Li et al . that adjusted serum calcium is associated with an increased risk of left ventricular hypertrophy in patients with type 2 diabetes.…”
Section: Resultsmentioning
confidence: 95%
“…[11] Previous studies reported that high normal calcium levels are associated with greater pulse wave velocity in 9165 Chinese subjects, [18] carotid plaque thickness in 1194 multiethnic subjects, [19] and increased risk of left ventricular hypertrophy in 833 Chinese diabetic subjects. [20] Recent data from a longitudinal study of 1507 middle-aged Japanese men, which found changes in brachialankle pulse wave velocity during a 3-year follow-up period, further highlight the possibility that increased serum calcium may be involved in the pathogenesis of atherothrombosis. [21] The biological mechanisms underlying the association between serum calcium concentrations and increased prothrombotic markers are unclear, but there may be several explanations.…”
Section: Discussionmentioning
confidence: 99%